1 - Can Africa Run? Industrialisation and Development in Africa - Fiona Tregenna (Africa Development, 2023)
Africa remains the least industrialised region in the world. Yet industrialisation is critical for growth and catching up, as well as for development more broadly. This article begins by discussing industrialisation in Africa through the lens of Thandika Mkandawire’s writings on the subject, within the context of his broader thinking on development. In particular, it reflects on his perspectives on structural change and industrialisation; the phases of industrialisation and deindustrialisation in Africa; the political economy of industrialisation in Africa; social policy and industrialisation; and trade and regional integration. The author provides an analysis of some key issues pertaining to industrial development and policy in Africa and argues that the weaknesses of industrialisation in Africa, and the periodic reversals through premature deindustrialisation, have not only hampered economic growth and development, but have also influenced the political economy of African countries, with wider social and political effects. Similarly, state capacity for industrial policy is built through ‘learning by doing’ in the actual practice of industrial policy. Amongst the key topical issues discussed in the article for industrialisation in Africa are upgrading and technological progress, regional integration, and the greening of industrialisation. A vision is put forward for ‘Transformative Industrialisation for Africa’ (TIfA).